Acquisition of resistance to androgen deprivation therapy in salivary duct carcinoma: A case report. (September 2018) - Wasano, Koichiro; Sakurai, Kouhei; Kawasaki, Taiji; Kusafuka, Kimihide; Kasahara, Masao; Kondo, Naoki; Inada, Ken-ichi; Ogawa, Kaoru
Salivary duct carcinoma is a relatively rare salivary cancer, and most cases are androgen receptor -positive. Salivary duct carcinoma growth is suggested to be androgen dependent, which can reportedly be controlled by androgen deprivation therapy. However, the effectiveness and underlying molecular mechanisms of androgen deprivation therapy for salivary duct carcinoma remain unknown. We report a salivary duct carcinoma case (65-year-old man) arising from the parotid gland with metastasis to the neck lymph nodes and lungs. Androgen deprivation therapy was performed according to the same protocol for prostate cancer treatment. Expression levels of androgen receptor and FOXA1 (forkhead box A1) were immunohistochemically analyzed before and after androgen deprivation therapy. Although the tumor volume was partially diminished during the first 3 months, acquired resistance to androgen deprivation therapy occurred. FOXA1 was not detected in parotid gland after androgen deprivation therapy, whereas androgen receptor expression was positive. FOXA1 expression might be related to acquired androgen deprivation therapy resistance in salivary duct carcinoma.